PENGARUH STIMULASI AUDITORIK TERAPI MUSIK TERHADAP NILAI GLASGOW COMA SCALE (GCS) PADA PASIEN CEDERA OTAK SEDANG - Enny Virda Yuniarti; Endah Dwi Astutik (STIKes William Booth Surabaya, 2016)
Brain injury is non-degenerative and non-cogenital abnormality of brain which is caused by the external mechanic trauma, so it can cause the cognitive unapropriate, physical and psychosocial function which can be temporary or permanent, realated to some levels of consciousness. The quantitive evaluation of consciousness by looking the Glasgow Coma Scale (GCS) is between 9 and 12. One of the auditory stimulations is by musical theraphy. Music can be functioned as the tool of health theraphy. Music has the electrical wave on the brain can be fasten or not, and at the same time, the body system activity will face changes. The research was done in the room of Kahuripan Prof.Dr.Soekandar Hospital with the population of 25 patients with medium brain injury which contains with GCS 9-12. Thus the sample with the correct criterion can be reached, that are 18 patients. The musical theraphy was given in three days, and then the data using non-probability sampling technique accidental sampling. Music therapy for 3 days and then do the tabulation of data was tested by using modus analysis. The value of Glasgow Coma Scale before the treatment of musical theraphy in the room of Kahuripan Prof.Dr.Soekandar Hospital was more than a half of the respondents (77,8%) with 10-11. The GCS value after the treatment, there were 12 respondents (66,7%) who have the rise of GCS value from 10 to 12. There was an influence of musical theraphy to the GCS value of the patients with medium brain injury in Kahuripan Room Prof.Dr. Soekandar Hospital, which was proved by the modus value before the treatmentwhich was only GCS 10, and after the treatment it became GCS 12.